PENGARUH LINGKUNGAN FISIK KELAS DAN DUKUNGAN ORANG TUA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Murtiasih, Diah (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2015)
The  research aims at  investigating:  (1) whether  there  is a  significant effect on physical classroom  environment  towards  the  learning  motivation  of  Grade  XI  Students  of  Office Administration  Skill  Competence  at  SMK  Negeri  I  Sukoharjo  (Vocational  School  I  Sukoharjo)  in Academic Year of 2013/2014; (2) whether there is a significant effect on parents? support towards the  learning motivation of Grade  XI  Students of Office Administration  Skill Competence at  SMK Negeri  I Sukoharjo  (Vocational School  I Sukoharjo)  in Academic Year of 2013/2014;  (3) whether there  is  a  significant  effect  on  physical  classroom  environment  and  parents?  support comprehensively  towards  the  learning motivation of Grade XI Students of Office Administration Skill Competence at SMK Negeri  I Sukoharjo (Vocational School  I Sukoharjo)  in Academic Year of 2013/2014.This  research?s  design  is  descriptive  quantitative.  The  population  of  the  research  is  72 students  of  Grade  XI  Students  of  Office  Administration  Skill  Competence  at  SMK  Negeri  I Sukoharjo (Vocational School I Sukoharjo) in Academic Year of 2013/2014. The samples which are taken by applying Simple Random sampling  technique are 43 students. Questionnaire  is used  to do  the data collecting method, and statistical  test with Double Regression Analysis  is applied as the data analysis technique.The  results  of  the  research  are:  (1)  there  is  a  significant  effect  on  physical  classroom environment  towards  the  learning motivation of Grade XI Students of Office Administration Skill Competence  at  SMK  Negeri  I  Sukoharjo  (Vocational  School  I  Sukoharjo)  in  Academic  Year  of 2013/2014.  It  is proved by the result of rcount > rtable or 0.430 > 0.310 on significance value of 5%. The  relative  contribution  is  29.40%  and  the  effective  contribution  is  6.19%;  (2)  there  is  a significant effect on parents? support towards  learning motivation of Grade XI Students of Office Administration  Skill  Competence  at  SMK  Negeri  I  Sukoharjo  (Vocational  School  I  Sukoharjo)  in Academic  Year  of  2013/2014.  It  is  proved  by  the  result  of  rcount  >  rtable  or  0.430  >  0.310  on significance  value  of  5%.  The  relative  contribution  is  70.60%  and  the  effective  contribution  is 14.87%;  (3)  there  is a significant effect on physical classroom environment and parents? support comprehensively  towards  the  learning motivation of Grade  XI Students of Office Administration Skill Competence at SMK Negeri  I Sukoharjo (Vocational School  I Sukoharjo)  in Academic Year of 2013/2014. It is proved by the result of Fcount > Ftable or 9.794 > 3.23 on significance value of 5%.From the result of the statistical count, it is known that the linear regression ? = 27.998 + 0.344 X1 + 0.319 X2 which means the learning motivation (Y) will increase or decrease as much as 0.344  for  each  increase  or  decrease  of  a  unit  of  class  physical  environment  (X1)  and  also will increase or decrease as much as 0.319 for each increase of decrease of a unit of parents? support (X2).  Keywords: class physical environment, parents? support, learning motivation